Antihyperglycemic and Hypolipidemic Effect of Azadirachta indica Leaves Aqueous Extract in Alloxan-Induced Diabetic Male Rabbits: Antihyperglycemic and Hypolipidemic Effect of Azadirachta indica Leaves Aqueous Extract in Alloxan-Induced Diabetic Male Rabbits - Al-Awar, Mohammed S. A. (International Journal of Pharmaceutical & Biological Archive, 2018)
Introduction: In the present study, the hypoglycemic potentials of Azadirachta indica (AI) were studied in rabbits.The animals were divided randomly into four groups: Normal control, diabetic control, and two diabetic treated with AI groups. Method: An aqueous extract of AI fresh leaves was administered daily (200 and 400 mg/kg, orally) for a period of 25 days to alloxan-induced diabetic rabbits. Fasting blood serum was analyzed for blood glucose, in the day 5, 10, 15, 20, and 25 (every 5 days), cholesterol, high-density lipo protein, low-density lipoprotein, and triacylglycerides levels in the day 25 (the past day of experiment). The alloxan-injected rabbits exhibited hyperglycemia, indicating their diabetic condition. Result: At a dose of 200 and 400 mg/kg, extract of AI was significantly effective in lowering serum glucose, and lipid profile levels in the AI-treated diabetic rabbits compared with the control diabetic rabbits. The present results indicate that AI possesses hypoglycemic and hypolipidemic potential. Conclusion: Thus, AI may be of great value in managing the hyperglycemia and some diabetic complications in human subjects.